PENGEMBANGAN MANAJEMEN PENGELOLAAN SAMPAH DI KOTA KUPANG MENJADI SAMPAH YANG BERNILAI EKONOMIS TINGGI: DEVELOPMENT OF WASTE MANAGEMENT IN KUPANG CITY INTO HIGH ECONOMIC VALUE OF WASTE - Serliyanti Ndun; Naomi Taneo; Helena Hibu (JURNAL WILAYAH, KOTA DAN LINGKUNGAN BERKELANJUTAN, 2022)
Along with human activities that continue to exist, it can be ascertained that the volume of waste will always increase along with the increasing consumerism of society every year. The impact is not only on the environment but also on human health. Therefore, a breakthrough in waste management is needed through the development of organic waste management in Kupang City into high economic value waste. The method used is a quantitative approach, namely to find out the stages of waste management in Kupang City and also the organic waste development model that needs to be done. Furthermore, a descriptive analysis was carried out on the opportunities for the use of organic waste in Kupang City, preceded by projecting the population of Kupang City. Afterwards, measurements of the composition and characteristics of household waste were carried out to determine the size of each component of the waste management system in Kupang City, which needed to be fixed from the source of waste. That was by sorting household organic and inorganic waste before being disposed of in a temporary dump according to the Government Regulation No. 81, year 2021, chapter 17, paragraph 1. However, the community does not comply with the existing regulations in reality. Therefore, it needs to be socialized to the waste-producing community. The stages of waste management in Kupang City are started by collecting waste from households, then the waste is transported using garbage carts or garbage motorcycles to temporary shelters at each point, and finally transported by garbage trucks to final disposal in Alak Village, Kupang City. The conversion of organic waste into high-value waste is accomplished by utilizing 67.5% of organic waste as biogas and compost.